'Big issues' in neurodevelopment for children and adults with congenital heart disease. Issue 2 (3rd July 2019) - Verrall, Charlotte E; Blue, Gillian M; Loughran-Fowlds, Alison; Kasparian, Nadine; Gecz, Jozef; Walker, Karen; Dunwoodie, Sally L; Cordina, Rachael; Sholler, Gary; Badawi, Nadia; Winlaw, David
Abstract : It is established that neurodevelopmental disability (NDD) is common in neonates undergoing complex surgery for congenital heart disease (CHD); however, the trajectory of disability over the lifetime of individuals with CHD is unknown. Several 'big issues' remain undetermined and further research is needed in order to optimise patient care and service delivery, to assess the efficacy of intervention strategies and to promote best outcomes in individuals of all ages with CHD. This review article discusses 'gaps' in our knowledge of NDD in CHD and proposes future directions.